2019
DOI: 10.1093/infdis/jiz166
|View full text |Cite
|
Sign up to set email alerts
|

No Correlation Between Nasopharyngeal Human Bocavirus 1 Genome Load and mRNA Detection or Serology in Adeno-/Tonsillectomy Patients

Abstract: Human bocavirus 1 (HBoV1) can persist in nasopharynx and tonsils. Using HBoV1 serology, reverse-transcription polymerase chain reaction (PCR) for detecting messenger RNA (mRNA) and quantitative PCR for HBoV1 genome load count, we studied to what extent the HBoV1 DNA loads in nasopharynx correlate with acute infection markers. Tonsillar tissue, nasopharyngeal aspirate, and serum were obtained from 188 elective adeno-/tonsillectomy patients. Relatively high loads of HBoV1 DNA were detected in the nasopharynx of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…Even if HBoV1 has been shown to often persist in tonsils, the mRNA data revealing viral activity, have been inconclusive (17,18). In our study, HBoV1 DNA persisted in pediatric adenotonsillar tissues at high prevalence; however, the diverse and often low viral loads (10 0 to 10 6 copies/10 6 cells) would rule against major productive replication.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Even if HBoV1 has been shown to often persist in tonsils, the mRNA data revealing viral activity, have been inconclusive (17,18). In our study, HBoV1 DNA persisted in pediatric adenotonsillar tissues at high prevalence; however, the diverse and often low viral loads (10 0 to 10 6 copies/10 6 cells) would rule against major productive replication.…”
Section: Discussioncontrasting
confidence: 61%
“…The virus is capable of productively infecting polarized pseudostratified epithelial cells, mimicking the in vivo milieu of the airway epithelium and causing cell hypertrophy and loss of cilia (2,21,22). HBoV1 DNA is very prevalent (up to 56%) in tonsillar tissues of children with tonsillitis or hypertrophy without symptoms of RTI (11)(12)(13)(14)(15)(16)(17)(18). A common treatment for such ailments is removal of adenotonsillar tissue, which has been shown to decrease the prevalence of particularly DNA viruses, like HBoV1 and adenoviruses, in the nasopharynx (19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 The diagnosis of acute bocavirus infection is based on quantitative polymerase chain reaction (PCR), expression of HBoV1 messenger RNA (mRNA), or serology, as the virus DNA may persist for weeks, even months. 1,[3][4][5][6] Interestingly, a few studies have found HBoV1 DNA in tonsil squamous cell carcinoma tumors, inducing speculations of a possible causal association. 7,8 Tonsils in the oropharynx are in contact with inhaled and ingested allergens and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…HBoV1 is typically found in such specimens from young children suffering with lower respiratory‐tract infections such as bronchiolitis, wheezing, asthma, or pneumonia 1,3 . The diagnosis of acute bocavirus infection is based on quantitative polymerase chain reaction (PCR), expression of HBoV1 messenger RNA (mRNA), or serology, as the virus DNA may persist for weeks, even months 1,3–6 . Interestingly, a few studies have found HBoV1 DNA in tonsil squamous cell carcinoma tumors, inducing speculations of a possible causal association 7,8 …”
Section: Introductionmentioning
confidence: 99%